Animated Movie Product to Train Ablution Practice - Lestari, Shania Nada Lestari; Azzahra , Viona; Tabroni , Imam; Jixiong, Cai; Xu, Shanshan (Journal Emerging Technologies in Education, 2023)
Background. This study aims to analyze the use of learning media at SDN 1 DANGDEUR and develop Capcut-based animated videos as an alternative to interesting learning media Purpose. The results of the initial analysis show that although the school has provided several learning media, the teachers tend to rely more on the blackboard and textbooks. Method. Learning media has an important role in facilitating the learning process and improving students' understanding. Therefore, this research encourages teachers to be more creative in using existing learning media. Results. , This research involves the stages of needs analysis, material content adaptation, learning media design, and Capcut-based animation video development. The results of this study show that the use of Capcut-based animated videos in learning has a significant effect on student learning achievement. Conclusion. There is a significant increase in students' average score after using this learning media